Examining the trend in agarwood oil studies for the 5 recent years (2019-2023): a comprehensive bibliometric analysis using VOSviewer - Mohd Yusoff, Zakiah; Nordin, Siti Aminah; Muhammad, Zuraida; Ismail, Nurlaila (UiTM Press, 2025)
This bibliometric article investigates the burgeoning research landscape surrounding agarwood oil, derived from the Aquilaria tree species. The historical and cultural significance of agarwood, coupled with its diverse applications in perfumery, traditional medicine, and religious practices, has fueled a surge in scientific interest. However, a comprehensive understanding of the current state of agarwood oil research is lacking. This study addresses this gap through a systematic review and bibliometric analysis, utilizing the SCOPUS database as the primary source of scholarly. By employing techniques such as co-citation analysis and keyword co-occurrence, the research aims to quantify patterns, relationships, and collaborations within the literature. The methodology involves a focused exploration of a specified timeframe to capture recent developments, with the anticipation that the outcomes will include the identification of key contributors, thematic clusters, and emerging trends in agarwood oil research. The study is poised to contribute valuable insights for researchers, policymakers, and industry stakeholders, offering a holistic perspective on the interconnectedness of agarwood oil research and guiding future exploration in this dynamic field.